2015
DOI: 10.1007/s11524-015-9956-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in a Brazilian Urban Slum Population

Abstract: Low-and middle-income countries account for the majority of hypertension disease burden. However, little is known about the distribution of this illness within subpopulations of these countries, particularly among those who live in urban informal settlements. A cross-sectional hypertension survey was conducted in 2003 among 5649 adult residents of a slum settlement in the city of Salvador, Brazil. Hypertension was defined as either an elevated arterial systolic (≥140 mmHg) or diastolic (≥90 mmHg) blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
2
17
2
Order By: Relevance
“…A 2012 survey in a Lima, Peru community found lower prevalences of hypertension and DM, but similar prevalences of overweight, obesity, and smoking to our survey [ 35 ]. Serial cross-sectional surveys from a Kenyan slum in 2010 reported similar prevalences of hypertension, a lower prevalence of DM and a higher prevalence of overweight and obesity compared to the present study [ 7 , 16 , 36 ]. Several other studies in Kenyan and Nigerian communities have reported a lower prevalence of hypertension than among those living in Pau da Lima [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A 2012 survey in a Lima, Peru community found lower prevalences of hypertension and DM, but similar prevalences of overweight, obesity, and smoking to our survey [ 35 ]. Serial cross-sectional surveys from a Kenyan slum in 2010 reported similar prevalences of hypertension, a lower prevalence of DM and a higher prevalence of overweight and obesity compared to the present study [ 7 , 16 , 36 ]. Several other studies in Kenyan and Nigerian communities have reported a lower prevalence of hypertension than among those living in Pau da Lima [ 8 , 10 ].…”
Section: Discussionsupporting
confidence: 67%
“…Existing surveys of NCDs and NCD risk factors in slums tend to focus on individual NCDs. Further, many studies done in urban areas do not disaggregate the population’s health data by slum and non-slums status to allow for the detection of intra-urban health disparities, or even sample from this population [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension awareness in Brazil ranges from half to more than two thirds of the population. Although in some Brazilian regions BP control was reported in 67,5% [13] , in most part of the country, BP control is reached in less than 40% of the hypertensive population [24] , [25] , [26] . A better BP control would be expected in Brazil as the Brazilian FHS covers most of the country.…”
Section: Discussionmentioning
confidence: 99%
“…50 Despite the fact that 1 billion of the world's population currently live under slum conditions or in other marginalized urban settlements in poorer countries, 51 research directly tying poor urban living conditions to hypertension in LMICs is still limited. [52][53][54][55] Studies from African cities, some of which may share urban and sociodemographic characteristics with Quibdó, have found an increase in blood pressure in urban compared with rural populations as a result of current urban residence and/or lifetime exposure to urban environments. 39,56,57 Most of these studies suggest that changes in well-established risk factors for hypertension, such as physical inactivity and stress, are involved in this increase.…”
Section: Discussionmentioning
confidence: 99%